Information and Communication Systems - Nagaraja B. G.; S. Kannadhasan (CRC Press, 2026)
This book looks closely at the latest insights and developments in information and communication systems, with particular emphasis on the use of advanced technologies like smart antennas, wireless communication, artificial intelligence, the Internet of Things (IoT), and signal processing.The chapters included in this volume connect theoretical principles with practical applications to explore a key theme – building reliable and sustainable communication infrastructures through noise-resistant speech technologies, network security, and advanced wireless systems. Taking a multidisciplinary approach, the research contributions contained in this book illustrate how the combination of intelligence and soft computing techniques with communication systems can improve performance, reliability, and scalability.The book is intended for researchers, academicians, industry professionals, and postgraduate students in rapidly evolving fields of electronics, communication engineering, and computer science. It will also benefit practitioners seeking practical insights into emerging technologies, as well as policymakers and innovators aiming to bridge academic research with industrial applications.The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC BY-NC-ND)] 4.0 license.